Addition of protein and amino acids to carbohydrates does not enhance postexercise muscle glycogen synthesis - Jentjens, R. L.; van Loon, L. C.; Mann, C. H.; Wagenmakers, A. J.; Jeukendrup, A. E. (Journal of Applied Physiology, 2001)
Ingestion of a protein-amino acid mixture (Pro; wheat protein hydrolysate, leucine, and phenylalanine) in combination with carbohydrate (CHO; 0.8 g · kg1 · h1) has been shown to increase muscle glycogen synthesis after exercise compared with the same amount of CHO without Pro. The aim of this study was to investigate whether coingestion of Pro also increases muscle glycogen synthesis when 1.2 g CHO · kg1 · h1 is ingested. Eight male cyclists performed two experimental trials separated by 1 wk. After glycogen-depleting exercise, subjects received either CHO (1.2 g · kg1 · h1) or CHO+Pro (1.2 g CHO · kg1 · h1 + 0.4 g Pro · kg1 · h1) during a 3-h recovery period. Muscle biopsies were obtained immediately, 1 h, and 3 h after exercise. Blood samples were collected immediately after the exercise bout and every 30 min thereafter. Plasma insulin was significantly higher in the CHO+Pro trial compared with the CHO trial (P < 0.05). No difference was found in plasma glucose or in rate of muscle glycogen synthesis between the CHO and the CHO+Pro trials. Although coingestion of a protein amino acid mixture in combination with a large CHO intake (1.2 g · kg1 · h1) increases insulin levels, this does not result in increased muscle glycogen synthesis.